Replica RISM molecular solvation theory for electric double layer in nanoporous materials - Andriy Kovalenko (Condensed Matter Physics, 2025)
Applications of 3D-RISM-KH molecular solvation theory range from solvation energy of small molecules to phase behavior of polymers and biomolecules. It predicts the molecular mechanisms of chemical and biomolecular systems. Replica RISM-KH-VM molecular solvation theory predicts and explains the structure, thermodynamics, and electrochemistry of electrolyte solutions sorbed in a nanoporous material. It was tested on nanoporous carbon supercapacitors with aqueous electrolyte and nanoporous electrosorption cells. The mechanisms in these systems are steered by the electric double layer potential drop across the Stern layer at the nanopores surface and the Gouy-Chapman layer averaged over the nanoporous material, the osmotic term due to the ionic concentrations difference in the two nanoporous electrodes and in the electrolyte solution outside, and the solvation chemical potentials of sorbed ions averaged over the nanoporous material. The latter strongly depends on chemical specificity of ions, solvent, surface functional groups, and steric effects for solvated ions confined in nanopores.